Protocol and project: the Oulipo and the process of writing - Andrews, Chris (Spunti e Ricerche, 2016)
For over forty years the collective of experimental writers known as the Oulipo has been inventing, testing and exploiting rules for literary composition. A working definition divides them into two categories. This article discusses in particular the particular category of Oulipo's rules which bear on the process of writing and have been called protocols. The various implications of publishing the protocols are examined. The protocol may work as a tool for the writer, but it also works on the reader.